Neural correlates of control over pain in fibromyalgia patients - Mosch, Benjamin; Hagena, Verena; Herpertz, Stephan; Ruttorf, Michaela; Diers, Martin (NeuroImage: Clinical, 2023)
The perceived lack of control over the experience of pain is arguably-one major cause of agony and impaired life quality in patients with chronic pain disorders as fibromyalgia (FM). The way perceived control affects subjective pain as well as the underlying neural mechanisms have so far not been investigated in chronic pain. We used functional magnetic resonance imaging (fMRI) to examine the neural correlates of self-controlled compared to computer-controlled heat pain in healthy controls (HC, n = 21) and FM patients (n = 23). Contrary to HC, FM failed to activate brain areas usually involved in pain modulation as well as reappraisal processes (right ventrolateral (VLPFC), dorsolateral prefrontal cortex (DLPFC) and dorsal anterior cingulate cortex (dACC)). Computer-controlled (compared to self-controlled) heat revealed significant activations of the orbitofrontal cortex (OFC) in HC, whereas FM activated structures that are typically involved in neural emotion processing (amygdala, parahippocampal gyrus). Additionally, FM displayed disrupted functional connectivity (FC) of the VLPFC, DLPFC and dACC with somatosensory and pain (inhibition)-related areas during self-controlled heat stimulation as well as significantly decreased gray matter (GM) volumes compared to HC in DLPFC and dACC. The described functional and structural changes provide evidence for far-reaching impairments concerning pain-modulatory processes in FM. Our investigation represents a first demonstration of dysfunctional neural pain modulation through experienced control in FM according to the extensive functional and structural changes in relevant sensory, limbic and associative brain areas. These areas may be targeted in clinical pain therapeutic methods involving TMS, neurofeedback or cognitive behavioral trainings.
Online verfügbar 21. Februar 2023, Artikelversion 26. Februar 2023
Gesehen am 17.05.2023